Potensi Implementasi Ekonomi Sirkular dalam Pengolahan Limbah Popok Bayi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
Baby diaper waste is categorized as Hazardous and Toxic Materials (B3) waste in Indonesia, with widespread usage. However, the absence of effective waste management or utilization systems has the potential to create environmental issues. Hence, there is a growing need to prevent environmental pollution stemming from baby diaper waste by applying the principles of a circular economy. This study aims to explore the potential implementation of a circular economy for managing baby diaper waste, as a step towards environmental sustainability. It involves identifying the existing conditions and characteristics of baby diaper waste through surveys with 260 parents of toddlers. The survey provides insights into diaper usage patterns, factors influencing diaper selection, and public knowledge regarding baby diaper waste. Furthermore, the research assesses the economic potential of processing baby diaper waste by a Community Self-Reliance Group (KSM) called